The Celebration: Analyzing realism in Dogme 95 Manifesto film - Dimas Raditya Bagaskara; M. Misbahul Amri; Nabhan Fuad Choiron; Evi Eliyanah (Fakultas Sastra Universitas Negeri Malang, 2022)
The Celebration: Analyzing realism in Dogme 95 Manifesto filmBelieving that the film industry is getting worse by utilizing simple plots and only emphasizing on the editing and the cosmetics, European filmmakers and theorists make their own style of realistic film movements as a reaction to Hollywood’s mainstream filmmaking style. One of which is the famed Dogme 95 Manifesto film movement in Denmark propagated by Lars von Trier. Dogme 95 Manifesto is a set of rules that needs to be followed by filmmakers in order to make a Dogme film. It is believed that by following this rule will restrain the filmmakers’ creativity, focusing more on the realism inside the film, and “purifying” the film industry. In this paper, we analyze realism in Dogme 95 through one of its successful milestones: The Celebration by Thomas Vinterburg through its cinematography and Dogme 95 rules within the film. We argue that as opposed to bringing realistic images on the screen, The Celebration brings atmospheric realism by providing a consistent feel of ‘relatability’ and presence inside the story to the spectators.The Celebration: Analisis realisme pada film Dogme 95 ManifestoSetelah mengetahui semakin parahnya industri film sekarang yang hanya menggunakan plot mudah dan lebih fokus kepada proses pengeditan dan kosmetik belaka, pembuat dan ahli film di Eropa telah membuat gaya film realis ciptaan mereka sendiri sebagai sebuah bentuk protes terhadap film-film mainstream ala Hollywood. Salah satunya adalah gerakan film Dogme 95 Manifesto asal Denmark yang digagas oleh Lars von Trier. Dogme 95 Manifesto berisi sebuah peraturan yang harus ditaati oleh pembuat film untuk membuat sebuah film Dogme. Mengikuti aturan-aturan ini akan lebih mengekang kreativitas para pembuat film, membuat film lebih realistis, dan mensucikan industri film. Dalam penelitian ini, kami menganalisis realisme dalam proyek Dogme 95 dari salah satu film mereka yang paling terkenal yaitu The Celebration yang disutradarai oleh Thomas Vinterburg dengan menggunakan analisis intrinsik berdasarkan aturan sinematografi dan aturan Dogme 95 yang ada di dalamnya. Para peneliti menyimpulkan bahwa tanpa perlu mempresentasikan kualitas gambar terbaik, The Celebration telah membawakan suasana realisme dengan memberikan nuansa ‘berada dalam cerita’ kepada para penonton.